Las publicaciones oficiales. Estado actual de la cuestión - García Sánchez, Mª Isabel (Revista General de Información y Documentación, 2009)
This article explores the current structure and development of a number of national, regional, local and European Union official publications. It builds on the principle of enactment of the rule by disclosure, understood as a guarantee for the citizen in democratic systems. The use of new technologies and the coexistence of hardcopy and electronic versions are the current key topics of concern for the management of official publications. The legal implications of these topics are discussed in depth in this piece of work.
Keywords: Official publications; Publicity of the rule; Electronic publications